The Applying Vocal Stage Performance for Teaching the Senior Vocal Music Students in Hui Zhou University of Guangdong in China: A Case Study of Chinese Operetta “Zai Bie Kang Qiao (Saying Good-bye to Cambridge again)” - Yi, Huang; Roongruang , Panya; Kongkumnerd, Tanit (Journal of Roi Kaensarn Academi, 2023)
The art of vocal music is a comprehensive art form which arouses the audience’s emotional resonance through vivid performance with language and human voice. Objectives of this research were (1) Studying teaching method of vocal stage performance from the expert. (2) The Construct a Vocal Stage Performance Guidebook teaching. (3) Using guidebook for teaching students. (4) The measure the results of teaching and evaluation for students’ satisfaction. This research used mixed method research and experimental study research. The researcher efficiency of the vocal stage performance teaching with comprehensive student’s physiological and psychological development and to choose formative and summative test, experiments were conducted on 15 Third-Year Students at Hui Zhou University, Guang Dong, China in semesters 1, between September-December 2022, a 120 minute a week totaling 15 weeks of lesson plan trial. The results are as follows: (1) It is found that students should learn the basics of vocal singing and using stage performance. (2) The teaching guide book of vocal stage performance is constructed, and the practical teaching of vocal stage performance is discussed: combining vocal music teaching with stage performance training and practical teaching of opera works. (3) 15 weeks of teaching are used to teach 15 students with the same music level. (4) There are corresponding achievements in all three tests. The average score of the students in the 15th week was 83.30. According to the research hypothesis. Judging from the total score. Most students scored 100% of the high students in this test.